2023
DOI: 10.3390/agronomy13020279
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Biological and Proteinogenic Characteristics of Quinoa Genotypes as a Multi-Purpose Crop

Abstract: Quinoa is a multi-purpose vegetable, grain, and forage crop, due in part to the high nutritional value of its aerial parts. This work evaluates quinoa genotype characteristics as a starting point for a better understanding of multi-purpose cultivation. Ten cultivars of quinoa were studied on soddy-podzolic soils: Brightest Brilliant, Red Faro, and Cherry Vanilla from the US (USA 1–3); Titicaca (KY1) from Denmark; Regalo (KY2), a cultivar selected by the Baer Seed Research Center for southern Chile; as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…For instance, compared to the Castlerock and Fayrouz genotypes, the GS 12 hybrid showed higher biomass accumulation (plant height, number of leaves, and stem diameters). In this regard, various research studies showed variations in growth and development among different genotypes [50,51]. PGRs (BAP) probably enhanced the overall capability of the cells to produce essential organic compounds through biosynthesis [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, compared to the Castlerock and Fayrouz genotypes, the GS 12 hybrid showed higher biomass accumulation (plant height, number of leaves, and stem diameters). In this regard, various research studies showed variations in growth and development among different genotypes [50,51]. PGRs (BAP) probably enhanced the overall capability of the cells to produce essential organic compounds through biosynthesis [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…For the chemical analysis of African millet, samples were taken during three phases: the phase of emergence into the tube, heading, and flowering. The plant dry matter was determined by drying to a constant weight at 100-105 • C [26]. The chemical analysis of the samples was conducted at 25 • C and at a relative humidity of 45%.…”
Section: Methodsmentioning
confidence: 99%
“…The following parameters were measured: leaf number per plant, leaf area, fresh weight (FW), and dry matter. The dry matter content was determined by drying the leaves at 50 • C till a constant mass was achieved [42]. Moisture contents (MCs) were calculated using the leaves' fresh weight and dry matter.…”
Section: Determination Of the Morphological And Physio-biochemical At...mentioning
confidence: 99%